2018
DOI: 10.1111/vsu.13133
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A concentration in postoperative colic horses and its association with postoperative complications

Abstract: Objective: To determine serum amyloid A (SAA) concentrations in the postoperative (PO) colic horse and its association with PO complications and infection. Study design: Prospective case series. Animals: Fifty-one horses after colic surgery. Methods: Blood samples from horses undergoing exploratory celiotomy were analyzed for quantitative SAA and fibrinogen concentrations and for neutrophil count at days 0, 1, 2, and 4-6 and at hospital discharge. Results: Complications developed in 35 (69%) horses and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
14
3
1
Order By: Relevance
“…47 It is known that surgery itself, such as exploratory celiotomy for colic, causes an increase in APPs, including SAA. 43,[48][49][50] Compared with more minor surgical procedures, exploratory celiotomy causes a prolonged APR, with serum SAA concentrations increased from 48 to 96 hours after surgery (compared with 12-24 hours with minor procedures). 48,50,51 Horses with postoperative complications had a more pronounced increase in SAA (61.4-fold over baseline) and took longer to achieve peak values (96 hours) compared with horses without complications (29fold increase; peak at 48 hours).…”
Section: Gastrointestinal Disease and Serum Amyloid Amentioning
confidence: 99%
See 1 more Smart Citation
“…47 It is known that surgery itself, such as exploratory celiotomy for colic, causes an increase in APPs, including SAA. 43,[48][49][50] Compared with more minor surgical procedures, exploratory celiotomy causes a prolonged APR, with serum SAA concentrations increased from 48 to 96 hours after surgery (compared with 12-24 hours with minor procedures). 48,50,51 Horses with postoperative complications had a more pronounced increase in SAA (61.4-fold over baseline) and took longer to achieve peak values (96 hours) compared with horses without complications (29fold increase; peak at 48 hours).…”
Section: Gastrointestinal Disease and Serum Amyloid Amentioning
confidence: 99%
“…50 Another prospective study assessing SAA and complications in postoperative colic patients found that the magnitude of SAA increase was greater at 48 hours and 4 to 6 days postsurgery in horses with versus those without complications. 49 The data are conflicting regarding the accuracy and utility of SAA for determining outcome and prognosis in horses with colic. One study 44 found no significant differences in SAA concentration between survivors and nonsurvivors, whereas another larger study 50 of horses undergoing exploratory celiotomy found that patients with increased SAA concentrations 5 days postoperatively were slightly less likely to survive to discharge (odds ratio, 0.97).…”
Section: Gastrointestinal Disease and Serum Amyloid Amentioning
confidence: 99%
“…Preoperative measurement of [SAA] and [fibrinogen] has proved useful in evaluating potential gastro‐intestinal lesions, requirements for surgery and prognosis . However, the value of following trends in [SAA] and [fibrinogen] after exploratory celiotomy has only been reported in small numbers of horses (18 horses , 51 horses ). In man, [SAA] can be used to compare post‐operative outcomes between different surgical procedures .…”
Section: Introductionmentioning
confidence: 99%
“…In this prospective case study, Maia Aitken and colleagues in the USA aimed to determine serum amyloid A (SAA) concentrations in the post‐operative (PO) colic horse and its association with PO complications and infection .…”
Section: Saa Concentration In Post‐operative Colic Horsesmentioning
confidence: 99%